Analisis Bibliometrik Tren Penelitian Pengembangan Media Pembelajaran Geografi Tahun 2019 Sampai Tahun 2024 - Usman, Astin; Yusuf, Daud; Kobi, Wiwin (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the contribution of countries in scientific publications related to the development of Geography learning media during the period 2019 to 2024. The method used is bibliometric analysis using VOSviewer software, with publication data obtained through the Publish or Perish application and sourced from Google Scholar. The visualization results show that the United States is the country with the highest contribution in this study, as seen from the most dominant node size and central position in the collaboration network. Other countries such as China, Indonesia, India, and Germany also show significant levels of involvement, reflected in the number of collaborative relationships and large node sizes. On the other hand, the involvement of countries such as South Korea, Austria, Mexico, and Kenya is observed to be lower, with minimal connectivity intensity. These findings indicate that the issue of developing Geography learning media has become a global concern, with the dominance of contributions from countries that have strong research and education capacities